Pengaruh Good Corporate Governance terhadap nilai perusahaan pada perusahaan manufaktur sektor logam dan sejenisnya yang terdaftar di Bursa Efek Indonesia tahun 2017 – 2019 - Dwi Anggraeni Saputri; Keirstin Mauli Rogate Hutauruk; Ulfa Fitriyani Yapan; Hifni Pangestu (Indonesian Journal of Taxation and Accounting)
This study was conducted to test whether the disclosure of Corporate Social Responsibility (CSR) has an effect on firm value in metal sector companies and the like listed on the Indonesia Stock Exchange (IDX) in 2017-2019. From the results of this study it can be concluded that the variable Good Corporate Governance with the indicator of the Board of Directors has a significant effect on firm value by using Tobin's Q Ratio. This means that the company's board of directors has a considerable influence in the company's decision-making process to maximize firm value. Therefore, in order for decision making to be carried out accurately and quickly, the composition of the number of the board of directors must be considered.